Penerapan Metode Ward and Peppard dalam Analisis Infrastruktur TI pada Global Youth Action - Farica Rachman, Naura; Excel Ervinta Desty; Naura Arum Kartika; Ito Setiawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
Global Youth Action is a company engaged in youth empowerment with a focus on supporting the achievement of Sustainable Development Goals (SDGs) through the collaboration of various youth movements in Indonesia and internationally. However, the company still faces challenges in terms of infrastructure and information system (IS) applications that are not fully capable of supporting business processes optimally. One of the main obstacles is the limited human resources who have expertise in managing SI and information technology (IT) effectively. In preparing the SI strategic planning framework, this research uses the Ward and Peppard approach to analyze company needs. The analysis process includes mapping the company's internal and external environment through Value Chain Analysis and SWOT Analysis, as well as grouping the application portfolio using McFarlan Strategic Grid. The results of this research recommend the development of various applications such as the Global Youth Action Website application, SAP application, customer service information system, asset information system, and executive information system. These recommendations are expected to provide strategic direction for the global youth action company, as well as improve IT HR competencies and strengthen the application portfolio to support the sustainability of business processes at Global Youth Action.